Current Perspectives in microRNAs (miRNA) - Ying, Shao-Yao. (Springer, 2017)
Nearly 97% of the human genome is the non-coding DNA, which varies from one species to another, and changes in these sequences are frequently noticed to manifest clinical and circumstantial malfunction. Numerous non-protein-coding genes are recently found to encode microRNAs, which are responsible for RNA-mediated gene silencing through RNA interference (RNAi)-like pathways. MicroRNAs (miRNAs), small single-stranded 17a "25 nucleotide RNAs capable of interfering with intracellular messenger RNAs (mRNAs) that contain either complete or partial complementarity, are useful for the design of.